The effects of the European Union's and China's trade agreements on Africa's exports - Olayinka Idowu Kareem; Fatima Olanike Kareem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Empirical studies have shown that trade agreements have different effects on countries based on their level of development, especially in trade potentials. There have been several trade agreements between North-South and South-South countries, which are accompanied with different outcomes based on output, macroeconomic stability and compliance with the agreements reached. This study evaluates the effects of Africa's trade agreements with the European Union (EU) and China on Africa's exports. This study found that trade agreements in both trade relations have not brought any significant increment to Africa's exports and that more market access conditions exist in South markets than in the North markets.
Keywords: F10; F13; C23; 330; trade agreements; exports; panel data; Handelsabkommen; EU-Staaten; China; Afrika